AN ANALYSIS OF GRAMMATICAL ERRORS COMMITTED BY STUDENTS IN WRITING COMPARISON AND CONTRAST PARAGRAPHS - Yudhayana, Candra Dwi; Juniarta, Putu Adi Krisna (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Writing skills are still lacking and weak in students' classes and are often ignored by students. This study aimed at analyzing, and calculating the types and the sources of grammatical errors committed by the second-semester students from four classes in the English Language Education department academic year 2020/2021 in their comparison and contrast paragraphs. The final semester test of the Paragraph Writing course was used as the instrument of the study. Additionally, in analyzing the data, the theory by Dulay, Burt, and Krashen (1982) was used to describe the types of errors and the theory by Richards (1974) was used to analyze the errors’ sources. After that, that data was calculated. From the 114 paragraphs, 38 paragraphs that contained erroneous sentences were found. Four types of errors were classified, namely omission with 61 errors or 65%, followed by addition with 23 errors or 25%, then misformation with 6 errors or 6%, and the lowest was misordering with 4 errors or 4%. The errors were committed because of two sources; the first was an interlingual error that occurred 52 times or 54.84% and the second was an intralingual error with 42 errors or 45.16%. Conclusively, the omission and addition errors were the errors that needed to be concerned about because these two types of errors showed a very significant number of occurrences. Therefore, the students should be more aware of the grammar rules and teachers should emphasize the appropriate teaching method or technique to prevent the same errors to be happening in the future.